2DrowSys: an anti-drowsiness device for motorcyclists - Silva, Pablo Ricardo Roxo; Marques Neto, Manoel Carvalho (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2021)
Drowsiness is a problem that affects traffic on a worldwide scale, especially among motorcyclists, who use a naturally dangerous means of transport. Nowadays, there is no product on the market that performs an anti-drowsiness action in this public. This article aims to propose the creation of a wearable device coupled to the motorcycle helmet that detects a state of drowsiness through sensors and combats it using actuators. Still at an early stage, a prototype was created, tests in a controlled environment were carried out, preliminary results were presented and a series of future works were drawn up to continue the project.